SARS-CoV-2 Infection in Kidney Transplant Recipients: A Single-Centre Study of 20 Cases from India - Ravi Raju Tatapudi; Venkateswara Rao Kopparti; Anusha Poosapati; Srinivas Metta; Atchyutha Rao Gongada; Balakrishna Vedulla (International Journal of Nephrology)
Introduction. The second wave of COVID-19 has spread across India causing unprecedented misery to people since March 2021. Kidney transplant recipients (KTRs) are at an increased risk of severe infection. Their outcomes appear to be worse than those in the general population. There is no robust evidence or consensus to support any form of treatment protocol or modification of immunosuppression in KTRs with COVID-19. There is a need to develop effective and safe therapeutic protocols for this frail population. Remdesivir is the only approved antiviral drug in COVID-19 till now. Methods. We describe clinical features, role of HRCT, therapeutic protocols, and mortality rate of 20 KTRs with SARS-CoV-2 infection. Results. Complete recovery was seen in 8 (40%) patients monitored at home. 12 (60%) patients with HRCT scores more than 8/25 were hospitalized. 11 (55%) had hypoxia, of these 8 (40%) had mild hypoxia, 1 (5%) required NIV, and 2 (10%) needed mechanical ventilation. Immunosuppression was modified in all the patients. Remdesivir and dexamethasone were administered to the hospitalized patients. 1 (5%) patient had AKI requiring RRT. 1 (5%) patient expired, and 1 still hospitalized. 10 of the hospitalized patients recovered. Out of the total 20 patients, 18 (90%) recovered completely within two weeks of infection. Conclusion. Clinical presentation of COVID-19 in KTRs was similar to nontransplant patients. Early hospitalisation and assessing the severity by HRCT were important. Continuing tacrolimus and administering remdesivir and dexamethasone reduced the incidence of renal failure and improved survival rates.